The Impact of AI-Powered Mobile Money System on Supply Chain: Multi-Cases from SMEs in the Global South - Mohamad, Mostafa; Nii Laryeafio , Michael; Koroye, Ebimoboere; Nyame , Derick; Ayertey , Samuel; Emini , Adelina (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study explores the effects of adopting an artificial intelligence (AI)-powered mobile money system (AI-MMS) on supply chain operations among small and medium-sized enterprises (SMEs) in the Global South. The authors developed a new version of Rogers’ Diffusion of Innovation model (DoI) that considers the geopolitical context and environmental factors, including regulatory framework, trust, risk and complexity, to help understand how AI-MMS can enhance transactional efficiency in SMEs and bridge the financial inclusion gap. Using qualitative methods, we conducted 40 semi-structured interviews with SME owners in Abuja, Lagos, Kaduna, Kano and Port Harcourt and found that AI-MMS enhanced their logistics knowledge, increased system trust and helped overcome fraud along their supply chains. We also found that new economic forces have emerged because of the successful diffusion of AI-MMS in Nigeria. Our study contributes to the emerging debate on how AI-human intelligence in mobile technologies reshapes the economy and geopolitical context in developing nations. The paper also contributes to the practices of AI-MMS and how it enhances supply chain and logistics learning for SMEs in Nigeria and other countries with a similar geopolitical context.